Isolation and regeneration of cellulose fiber from sugarcane bagasse - Yeo, Madeline Geok Kim (Universiti Malaysia Sarawak (UNIMAS), 2012)
Sugarcane bagasse is the by-product obtained after sucrose extraction from sugarcane plant. However, the remaining bagasse is disposed and resulted in environmental pollution. Sugarcane bagasse has high proportion of cellulose, lignin and hemicelluloses. Sodium hydroxide used to remove lignin and hemicelluloses. Acetic acid and sodium chlorite was use to bleach the cellulose. FTIR results indicated that lignin and hemicelluloses has removed. Mechanical treatment by ultrasonic and homogenizer on isolated cellulose showed surface destruction on the cellulose through scanning electron microscopy (SEM) images. Furthermore, NaOH: Thiourea: Urea with the composition (8:6.5:8) was used as aqueous based solvent system in cellulose dissolution process. Ethanol acts as a non-solvent successfully precipitate the regenerated cellulose. The yield of regenerated cellulose increases as volume of the added ethanol increase.